Interval-index technology of synthesis of the parallel algorithms for modular-point code conversion with the table-summation configuration - A. A. Kolyada; P. V. Kuchynski; A. F. Chernyavsky (Наука. Инновации. Технологии, 2022)
The article describes the basic principles of interval-index technology of synthesis transformation algorithms minimally redundant modular code in the position code. The proposed algorithms are based on the direct implementation of interval- modular form of interval numbers using an index that has a very simple computational structure. Shows the new modular parallel procedure-point code conversion. Estimates are obtained for the development of effective representation.